Pengembangan Ekowisata Pada Atraksi Makepung Berbasis Kearifan Lokal Di Desa Tuwed, Kecamatan Melaya, Kabupaten Jembrana. - Sarka, I Ketut (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2026)
Tuwed Village, located in Melaya District, Jembrana Regency, is known for its mekepung tradition, a daily activity of Subak Tamansari Puspa farmers. Buffaloes are used as the primary source of power for plowing rice fields and transporting crops. This study aims to formulate strategies, the role of the local community, and the implications for developing Mekepung as a sustainable, local wisdom-based tourist attraction in Tuwed Village, Jembrana. The Mekepung tradition, rooted in the Subak Tamansari Puspa agricultural system, originally served as a means of transporting crops and providing post-harvest entertainment, with buffalo having functional, social, and ritual value (Tumpek Kandang). The background of this study is the significant decline in the buffalo population and the potential erosion of this tradition due to agricultural modernization (the use of tractors). This necessitates strategic conservation efforts through ecotourism, including strategies for developing tourist attractions, community roles, and implications for the socio-cultural, economic, and environmental aspects of Tuwed Village. This research employed a descriptive qualitative method, collecting data through direct field observation, in-depth interviews with Subak farmers, traditional leaders, and tourism stakeholders, and documentation studies. The research data indicates that the majority of Subak farmers revere buffalo, but are now shifting to modern technology. The study concluded that ecotourism development strategies should center on integrating Mekepung with the Subak system, organizing scheduled events, and developing derivative products. The key to sustainability is the active participation of the community as key actors. The implications of this development are positive, namely preserving the cultural and spiritual values ​​of buffalo, diversifying incomes for farmers, and encouraging the conservation of buffalo populations and the Subak environment. Mekepung is transforming from a work tool into a sustainable cultural asset.